Materials for Nuclear Waste Immobilization - Ojovan, Michael I (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The book outlines recent advances in nuclear wasteform materials including glasses, ceramics and cements and spent nuclear fuel. It focuses on durability aspects and contains data on performance of nuclear wasteforms as well as expected behavior in a disposal environment.